2015
DOI: 10.21769/bioprotoc.1514
|View full text |Cite
|
Sign up to set email alerts
|

Mouse Models of Uncomplicated and Fatal Malaria

Abstract: Mouse models have demonstrated utility in delineating the mechanisms underlying many aspects of malaria immunology and physiology. The most common mouse models of malaria employ the rodent-specific parasite species Plasmodium berghei, P. yoelii, and P. chabaudi, which elicit distinct pathologies and immune responses and are used to model different manifestations of human disease. In vitro culture methods are not well developed for rodent Plasmodium parasites, which thus require in vivo maintenance. Moreover, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
47
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(51 citation statements)
references
References 9 publications
2
47
0
2
Order By: Relevance
“…Mice were infected with 10 6 Plasmodium chabaudi AS (MRA-429; MR4 Stock Center) parasitized RBCs, and parasitemia was monitored by thin film blood smear as described [86]. Where noted, mice were injected i.p.…”
Section: Methodsmentioning
confidence: 99%
“…Mice were infected with 10 6 Plasmodium chabaudi AS (MRA-429; MR4 Stock Center) parasitized RBCs, and parasitemia was monitored by thin film blood smear as described [86]. Where noted, mice were injected i.p.…”
Section: Methodsmentioning
confidence: 99%
“…Parasite suppression and antimalarial effect of the lemon decoction as evaluated using Rane's curative test employing Plasmodium berghei parasites. Is an good model for studying pathological features associated with malaria infections as well as the primary screening for natural products with antimalarial activity [21]. In this study lemon decoction (CILI extract) has shown some antimalarial effect by suppressing parasite growth as depicted in Table 3.…”
Section: Discussionmentioning
confidence: 92%
“…Toxoplasma gondii is frequently used as a model organism for other apicomplexa due to its genetic and biochemical manipulability (Li and He 2017; Meyer, Caton, and Shapiro 2018; Sidik et al 2016; Kim and Weiss 2004). Mouse models of malaria (Huang, Pearman, and Kim 2015; Minkah, Schafer, and Kappe 2018) and cryptosporidiosis (Ward 2017; Sateriale et al 2019) imperfectly represent the disease and/or use different species than the human pathogen. However, the modest characterization of functional differences among parasite species limits the utility of this extrapolation-based approach.…”
Section: Introductionmentioning
confidence: 99%